2018
DOI: 10.1002/cphc.201800313
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Interaction of Ruthenium (II) Imidazole Phenanthroline Complex [Ru(bpy)2ipH]2+ with 1,4‐Benzoquinone: Simple Electron Transfer or Proton‐Coupled Electron Transfer?

Abstract: The unidirectional proton coupled electron transfer (PCET) from the excited state of Ru(II) imidazole phenanthroline complex [Ru(bpy) ipH] to 1,4-benzoquinone, was studied by steady-state (SS) and time-resolved (TR) fluorescence and transient absorption (TA) measurements. The pK (9.7) and pK * (8.6) values of the complex suggest that it behaves as a photoacid on excitation. The difference in the quenching rates obtained from SS and TR fluorescence studies indicate participation of both dynamic quenching and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…From the inflection point of the titration curve obtained by plotting the absorbance changes at 287, 316, 349, and 405 nm as a function of the proton concentration in the solution (cf. Figure S1b,c), 7,9,13,34 a pK a,1 value of approximately 2 for both complexes, corresponding to a deprotonation of the imidazolium cation, is obtained. Previous studies on Ru(II) complexes bearing an ip ligand have reported similar pK a values.…”
Section: ■ Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…From the inflection point of the titration curve obtained by plotting the absorbance changes at 287, 316, 349, and 405 nm as a function of the proton concentration in the solution (cf. Figure S1b,c), 7,9,13,34 a pK a,1 value of approximately 2 for both complexes, corresponding to a deprotonation of the imidazolium cation, is obtained. Previous studies on Ru(II) complexes bearing an ip ligand have reported similar pK a values.…”
Section: ■ Introductionmentioning
confidence: 85%
“…Both the absorptivities at 288 nm and at around 470 nm (shoulder) increase, while the absorption band at 316 nm vanishes. 7,20,35 The existence of three isosbestic points at 327, 390, and 435 nm during the spectrophotometric base-titration (from 1 up to 500 molar equivalents of base) demonstrates that only two absorbing species, namely, Ru-im and Ru-im − , are observed and thus a single deprotonation step occurs. The obtained pK a,2 value of 10, corresponding to the deprotonation of the secondary amine (cf.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GS pK a value of the imidazole group is about 19.8 ± 0.3 in the three complexes. Furthermore, a photoacid behavior of complexes bearing an imidazole unit fused to a ruthenium chromophore has been reported in the literature [14,27]. This property appears amplified in presence of ester-substituted bipyridine ligands, as clearly evidenced by the observed reversible flash-induced deprotonation of complex 3 in presence of a base, visible as a red-shift of the MLCT band of the ruthenium chromophore (Fig.…”
Section: Acid-base Properties Of the Complexesmentioning
confidence: 55%